2012
DOI: 10.1680/nme.12.00030
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-derived ceramics as anode material for rechargeable Li-ion batteries: a review

Abstract: Lithium ion batteries (LIB) is currently the most promising of all battery technologies for effi cient storage of electrical energy and powering of electric vehicles. However, the ongoing LIB research faces multiple issues pertaining to materials, cost and safety. One of the major factors that dictate the performance of LIB is its electrode's Li-storage (anode/ cathode) capacity, cycleability and effi ciency. In this article, the authors evaluate the recent experimental progress made in LIB anode materials pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 74 publications
0
37
0
Order By: Relevance
“…Graphene is a single tightly packed sheet of carbon atoms that are bonded together to form a hexagonal honeycomb lattice . There has been interest in integrating graphene in PDCs to alter their physical properties . For example, SiCN‐graphene composite anodes were fabricated, in which graphene sheets were inset in the ceramic network of SiCN .…”
Section: Introductionmentioning
confidence: 99%
“…Graphene is a single tightly packed sheet of carbon atoms that are bonded together to form a hexagonal honeycomb lattice . There has been interest in integrating graphene in PDCs to alter their physical properties . For example, SiCN‐graphene composite anodes were fabricated, in which graphene sheets were inset in the ceramic network of SiCN .…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] The silicon oxycarbide (SiCO) anode shows good electrochemical performance in terms of Li insertion, and recent experiments revealed that the storage capacity of SiCO ceramic materials is three times larger than that of graphite; [6][7][8][9][10][11] in particular, the silicon-centered tetrahedrons in SiCO sequester an equivalent of $50 000 mA h g À1 per atom. The graphite-based anode material used in commercial Li-ion batteries has a specic capacity of 372 mA h g À1 , 1,2 and this level of capacity places limitations on the energy densities that can be attained for many types of recently developed portable equipment.…”
Section: Introductionmentioning
confidence: 99%
“…They are covalently bonded ceramics, generally synthesized through controlled thermal decomposition of certain organosilicon polymers such as polysilazane, polysiloxanes, polycarbosilanes, and polyborosilanes in inert atmosphere. The excellent properties of PDCs may be attributed to their temperature‐dependent microstructure, which consists of −sp 2 ‐bonded carbon networks along with nanodomains of silicon mixed‐bond tetrahedra that resist crystallization up to approximately 1300–1500°C …”
Section: Polymeric Materials In Li‐ion Cellsmentioning
confidence: 99%
“…These issues may be addressed by altering the chemical structure of the starting polymer (and hence, the final ceramic), increasing surface area (by inducing porosity and surface etching), or adding electrically conducting nanofillers with a favorable chemical composition. Much of the work involving PDC anodes has been concentrated on polysilazane‐derived SiCN and polysiloxane‐derived SiOC systems …”
Section: Polymeric Materials In Li‐ion Cellsmentioning
confidence: 99%